Implementação dos serviços de comunicação e monitoração em um ambiente para desenvolvimento de sistemas distribuídos - Góis, Lourival Aparecido de (2002)
The TEV (Teaching Environment for Virtuoso) environment is a set of teaching tools that support the phases of analysis, design, implementation, depuration and test of real-time applications which are executed using the Virtuoso (Virtual Single Processor Programming System) kernel. This environment allows the application designer to graphically define the application data structures through an editor, write the C language code of the tasks and functions of the application and, finally, generate the necessary files to compile the application. These facilities solve most of the problems while generating of real-time applications, however, they do not support distributed applications. This master research aims at modeling and implementing an API (Application Programming Interface), based on TCP/IP protocols, to be used together with the TEV environment in order to provide some functionality related to real-time application generation on a network structure as well as to deal with some problems related to transparency in the communication between the protocols and the application processes. Based on this API, a generator, called AGAD, was developed to be used in the implementation and monitoring of the tasks involved with the communication. This work presents the API modeling, its utilization on the creation of the AGAD and the integration of the with TEV.